Hepatitis C virus infection in jail: Difficult-to-reach, not to-treat. Results of a point-of-care screening and treatment program. Issue 5 (May 2020) - Masarone, Mario; Caruso, Rosa; Aglitti, Andrea; Izzo, Carmine; De Matteis, Giuseppe; Attianese, Maria Rosaria; Pagano, Antonio Maria; Persico, Marcello
Abstract: Background: An unmet objective in the pursuit of HCV elimination is the creation of a simple and fast operating model to identify difficult-to-treat populations, like prisoners. Of many obstacles, the first is represented by the poor knowledge of inmates HCV-Ab prevalence. Moreover, due to the peculiar status of conviction, often their access to antiviral therapy is neglected. Aims: To evaluate the prevalence of HCV infection in a penitentiary Institution of Southern Italy through a point-of-care screening and treatment program. Methods: We conducted a prospective observational study in two phases: first, we reviewed all the prisoners' clinical records, to verify HCV-Ab execution. Subsequently, we performed a universal point-of-care screening and treatment program. Results: We enrolled 670 patients. Overall, 310(46.27%) were already HCV-Ab tested. At the screening initiation, 23.28% patients were discharged, whereas 8.35% refused. Of the remaining 458 subjects, 58(12.67%) were HCV-Ab positive and 46 HCVRNA positive. All these underwent DAA, obtaining 100% SVR. At the end of the program, a total of 491(73.28%) subjects had HCV-Ab available. Sixty-nine (14.05%) were positive. A total of 214(31.94%) subjects were lost to follow-up. Conclusions: We revealed a prevalence of 14.05% of HCV-Ab in conviction. Antiviral treatment was safe and efficacious. More efforts are advisable to provide screening for HCV-Ab in conviction.